Desert Related Death - Mohammed Madadin (MDPI AG, 2021)
Introduction: Desert death is defined as any death that occurs in the desert and could be attributed to a list of causes including environmental, animal related, undetermined, and other causes. Death in the desert seems to be obscure and little discussed in the field of forensic medicine, despite its importance, and there is only limited literature available on this broad topic. This narrative review aims to identify the most common causes of desert death and its medicolegal implications. Desert death causes: Environmental causes of death could be a result of temperature and lightening-related causes. Moreover, a variety of animals found in deserts are considered to be threatening and fatal, in addition to other and undetermined causes. Medicolegal implications of desert death: Likely to arise from the difficulties faced in finding the cause of death are the identification of the victim and the postmortem injuries that occur. Conclusion: Desert death is a broad topic with great medicolegal significance. More information and case reports need to be added in the literature. Guidelines for people about the danger of going to deserts in specific weather conditions should be implemented. Safety regulations must be taken into account at all times.